Quality Management Analysis in Improving the Quality of Sawo Products in Sukatali Village - Nursilawati, Usi Nabila; Pratami, Yessika Meira; Susilawati, Ingeu Eka; Kurniawan, Andrian; Agung, Muhamad Adila Permana Agung; Rahmawati, Wati; Auliyanti , Hera (SINTESA, 2025)
The goal of this study is to determine ways to raise the standard of sawo goods in Sukatali Village. Finding out how sawo traders raise the caliber of their goods is the aim of this study. A qualitative research approach utilizing observation, documentation studies, and interviewing methodologies is employed in this study. Researchers spoke with rw and kuwu, two of the four sawo traders, in order to gather information. The products on display demonstrated that Sukatali Village consistently maintains the high quality of its sawo products, as indicated by the findings. The way to improve the quality of sawo products is by picking sawo on time and ready to harvest and choosing old sawo.